Aesthetic theology in the Franciscan tradition the senses and the experience of God in art - Seubert, Xavier J. 1944-; Bychkov, Oleg V. 1966- (Routledge research in art and religion, 2020)
"The book investigates the aesthetic theology embedded in the Franciscan artistic tradition. The novelty of the approach is in applying concepts gleaned from Franciscan textual sources to create a deeper understanding of how art in all its sensual forms was foundational to the Franciscan milieu. Chapters range from studies of statements about aesthetics and the arts in theological textual sources to examples of visual, auditory, and tactile arts communicating theological ideas found in texts. The essays cover not only European art and textual sources, but also Franciscan influences in the Americas found in both texts and artifacts"--